Pengaruh Jumlah Kasus HIV/AIDS dan Cakupan Rumah Sehat terhadap Jumlah Kasus Tuberkulosis di Provinsi Jawa Timur - Rosalia Nur Hakim (Universitas Airlangga, 2018)
Tuberculosis is a disease caused by bacterial infection of Mycobacterium tuberculosis that can be transmitted from the patient to the surrounding environment including humans, which attacks the lung organ and other organs in the body. Based on the epidemiological triangle, infectious diseases are caused by 3 factors such as agent factor, host and environment. One of the host factors of Tuberculosis is HIV/AIDS, where many Tuberculosis infections are common in people with HIV/AIDS. From environmental factors causing Tuberculosis disease is a condition of less healthy house. Tuberculosis incidence in East Java Province in 2015 amounted to 44,063 which increased from 2014 that is as much as 42,475. This research was conducted to analyze the influence between HIV/AIDS and healthy house case against Tuberculosis incident in East Java Province. This research is a kind of analytical research using non-reactive method. The research sample used is total population consist of 29 regencies and 9 cities in East Java Province. Technical analysis of the research using multiple linear regression test. The results showed that there was a significant influence between HIV/AIDS cases on Tuberculosis occurrence in East Java (p-value = 0,000), and there was no significant influence between healthy house on Tuberculosis incidence in East Java Province. The conclusion of this study is that there is a significant relationship between HIV/AIDS cases and Tuberculosis cases in East Java Province. The HIV / AIDS and tuberculosis cases in East Java need to be improved by the Provincial Government of East Java such as providing information related to HIV/AIDS and Tuberculosis and screening HIV/AIDS.